A systematic review and meta-analysis of ventilator associated pneumonia in adults in Asia; an analysis of national income level on incidence and etiology - Bonell, A; Azarrafiy, R; Huong, VTL; Viet, TL; Phu, VD; Dat, VQ; Wertheim, H; Van Doorn, HR; Lewycka, S; Nadjm, B (Oxford University Press, 2018)
Background Ventilator-associated pneumonia (VAP) is the commonest hospital-acquired infection (HAI) in intensive care. In Asia, VAP is increasingly caused by resistant gram-negative organisms. Despite the global antimicrobial resistance crisis, the epidemiology of VAP is poorly documented in Asia. Methods We systematically reviewed literature published on Ovid Medline, Embase Classic, and Embase from 1 January 1990 to 17 August 2017 to estimate incidence, prevalence, and etiology of VAP. We performed a meta-analysis to give pooled rates and rates by country income level. Results Pooled incidence density of VAP was high in lower- and upper-middle-income countries and lower in high-income countries (18.5, 15.2, and 9.0 per 1000 ventilator-days, respectively). Acinetobacter baumannii (n = 3687 [26%]) and Pseudomonas aeruginosa (n = 3176 [22%]) were leading causes of VAP; Staphylococcus aureus caused 14% (n = 1999). Carbapenem resistance was common (57.1%). Conclusions VAP remains a common cause of HAI, especially in low- and middle-income countries, and antibiotic resistance is high.